Structural Features, Biosecurity and Animal Welfare Assessment in Sheep Farms in Yozgat Province, Türkiye - Aslan, A; Tüfekci, H (Journal of the Hellenic Veterinary Medical Society, 2025)
In this study, it was aimed to evaluate the sheep production enterprises in Yozgat province located in Central Anatolia Region of Türkiye in terms of production characteristics, general characteristics, biosecurity practices and animal welfare. The material of the study consisted of questionnaire, observation and measurement data obtained from 180 sheep production enterprises in Yozgat province. In the study, the general characteristics of the enterprises, flock management practices, shelter characteristics, feeding practices, health protection practices, biosecurity practices and welfare assessment were determined. As a result, sheep production in Yozgat province is mostly carried out with traditional methods and in the form of family enterprises. It is seen that some practices in the enterprises have deficiencies in terms of compliance with biosecurity parameters. In terms of welfare, according to the protocol developed from the ANI 35 L system, it was determined that the sheep farming enterprises in Yozgat province are mainly in the medium score categories in terms of protection from heat, protection from cold, suitable light and ventilation and number of drinkers from the parameters of shelter conditions; medium in terms of parameters other than milking parlour in terms of structure and equipment condition parameters; and high in terms of animal health parameters.